Der Roman Hundert Tage von Lukas Bärfuss - Požgan, Jure (Vestnik za tuje jezike, 2013)
This article analyses the literary representation of the Rwandan genocide in the novel Hundert Tage (One Hundred Days) by Lukas Bärfuss, a Swiss author. It focuses on the literature as a form of cultural memory and the question of its function in the history formation, i.e. in a self-reflexive confrontation with the Swiss post-colonial past. Through the problematisation of shared responsibility for genocide the author attempts to critically evaluate the role and guiltquestion of the international community, especially of Switzerland. David, the novels main protagonist, narrator and commentator, constantly questions his individual and collective guilt; therefore he symbolically reflects the attitude and the approach of the international community.Thus Bärfuss delivers his sharpest critique at the meta-level narration, where the excessive reproduction of the post-colonial discourse in the novel represents a stark contrast to the protagonist itself and offers an ironised, critically-reflexive assessment of the development policy as a policy for and not against genocide. The question of collective responsibility for the genocide remains unresolved and is merely compensated by the representation of resignation, apathy and helplessness of the international community in the presence of the largest humanitarian crisis after the Second World War.
Keywords: Bärfuss, Lukas, 1971-; Bärfuss, Lukas: Hundert Tage; švicarska književnost; German-language literature; nemška književnost; postkolonializem; genocid; Ruanda; Switzerland; Švica